2017
DOI: 10.1017/s1049023x17006665
|View full text |Cite
|
Sign up to set email alerts
|

Mass-Fatality Incident Preparedness Among Faith-Based Organizations

Abstract: The study suggests improvements are needed in terms of staff training in general, and specifically, drills with planning partners are needed. Greater cooperation and inclusion of FBOs in national planning and training will likely benefit overall MFI preparedness in the US. Zhi Q , Merrill JA , Gershon RR . Mass-fatality incident preparedness among faith-based organizations. Prehosp Disaster Med. 2017;32(6):596-603.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…After Hurricane Katrina in 2005, FBCOs were instrumental in providing assistance to those affected by the disaster (Pant et al, 2008 ). However, it has been noted that formal emergency preparedness plans among FBCOs are limited (Joshi, 2010 ; Zhi et al, 2017 ). Further, Joshi ( 2010 ) reported little collaboration among FBCOs, or between FBCOs and the government, has taken place.…”
Section: Discussionmentioning
confidence: 99%
“…After Hurricane Katrina in 2005, FBCOs were instrumental in providing assistance to those affected by the disaster (Pant et al, 2008 ). However, it has been noted that formal emergency preparedness plans among FBCOs are limited (Joshi, 2010 ; Zhi et al, 2017 ). Further, Joshi ( 2010 ) reported little collaboration among FBCOs, or between FBCOs and the government, has taken place.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, a tool was developed to assess the preparedness of CBHOs during biohazards. The researcher-made tool consisted of planning, training and infrastructure fields based on previous studies 7 8 27 30 31. After achieving face and content validity, CFA was used for the three-factor model fit.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in order to prevent the spread of Zika virus, organisations are expected to have very high communication skills to warn high-risk groups. In a study by Zhi et al ; they emphasised the need to educate the staff of faith-based organisations especially in exercises and drills 7. Eventually, Clawson et al examined the community health centres’ preparedness in the case of bioterrorism.…”
Section: Introductionmentioning
confidence: 99%
“…Recommendation 2: develop and/or expand current networks to include deathcare facilities and critical stakeholders In many cases, critical stakeholders to the deathcare community are excluded from the MFM planning process. For example, past surveys found that of those surveyed, only approximately 50% of health departments included access to spiritual counseling as part of their MFM plans, and only slightly more than half of faith-based organizations were assigned support functions in MFM plans (Merrill et al, 2017;Zhi et al, 2017). This means there is a need to incorporate these services into the MFM planning process.…”
Section: The Need For Innovationmentioning
confidence: 99%